Studies on the association of the Quercus suber decline disease with Phytophthora cinnamomi in Portugal - Moreira, A. C. (2012)
In Portugal, the decline disease has been described in evergreen oaks (Quercus suber L. and Q.ilex subsp. rotundifolia Lam.) since the end of the 19th century. The mortality of these species affects, particularly the central and southern regions of the country, being one of the most severe forest problems. Phytophthora cinnamomi Rands is the main pathogen responsible for the cork and holm oak mortality in Portugal. Several studies have been developed aiming at a better understanding of the effect of the P. cinnamomi action on the cork oak trees decline. The present work describes preliminary results of some of these studies.